SOCIO-PSYCHOLOGICAL METHODS OF MANAGEMENT - Dilshodbek T. Toshpolatov (International Scientific and Current Research Conferences, 2022)
Socio-psychological methods of management are means of managing producers and certain individuals by influencing their social needs and psychological characteristics. The use of socio-psychological methods of management requires a deep study of social phenomena occurring in the enterprise, knowledge of psychological (spiritual) factors affecting the mood of the nervous system of employees.